مفهوم الحداثة وتجلياتها في الشعر العربي القديم - مستاري, إلياس; تاوريريت, بشير (My University, 2017)
يقف القارئ في هذا المقال على تجذر مفهوم الحداثة في القواميس أو المعاجم العربية القديمة، وذلك من خلال الوقوف على مختلف المدلولات اللغوية لمصطلح الحداثة، وقد أردفنا هذا المدلول اللغوي بمدلولات اصطلاحية جمعنا شتاتها من الكتابات النقدية العربية المعاصرة. وقد سعينا في محطة ثالثة إلى التنقيب عن الأصول الإبداعية لتجليات الحداثة في الشعر العربي القديم،حيث وقع الاشتعال على التجليات الأولى للحداثة الشعرية في كتابات:بشار بن برد وأبو نواسوالمتنبيوأبو تمام.وقد مثلت تلك النتوءات إرهاصات أولى في التأسيس لمفهوم الحداثة الشعرية إبداعيا. This article sheds light on how the concept of modernism pervades the lexicon and dictionaries of classical Arabic, which could, firstly, be achieved through the examination of the different semantic facets of the term of "Modernism.". Secondly, the latter's meaning has been brought together with other terminological meanings that are gathered and adopted from contemporary critical studies. This study, thirdly, seeks to dig into how modernist creativity manifests itself and originates in Arabic classical poetry. In fact, the study focuses on the early manifestations of poetic modernism in the works of Bashar ibn Bord, Abu Nawas, Al-Mutanabbi, and Abu Tammam. Thus, one is likely to conclude that these early aspects of modernism could be considered as a pioneering step in the construction of the creative concept of poetic "Modernism."
Keywords: الحداثة، الشعر، الشعر العربي القديم; Modernity, poetry, ancient Arabic poetry